Divergent dynamics of surface water patterns and structures in Europe's coastal-zone basins - Liumeng Chen; Yongchao Liu; Jialin Li; Chao Ying; Peng Tian; Wenfei Kuang; Qiyu Huang; Tian Zheng (Ecological Informatics)
Surface water bodies are essential components of terrestrial ecosystems and play critical roles in sustainable development. Coastal-zone basins (CZBs), shaped by human activity and land–sea interactions, have undergone rapid urban expansion, landscape fragmentation, wetland degradation, and increased flood risk. However, comprehensive analyses of surface water dynamics in coastal zones on a continental scale are limited. This study examines the spatiotemporal evolution of surface water in Europe's CZBs, a region with a long history of development. The water bodies were classified into five types: weak seasonal water bodies (WSWBs), seasonal water bodies (SWBs), weak permanent water bodies (WPWBs), strong permanent water bodies (SPWBs), and permanent water bodies (PWBs). Using Landsat remote-sensing imagery from 1984 to 2023, we assessed the intensity of water-body transformations. WSWBs dominated the surface water composition, accounting for 76.94 % of the total, with concentrated patches in the eastern CZBs and sporadic distributions in the west. PWBs, comprising only 1.35 %, were primarily located in the Balkan, Apennine, and Iberian Peninsulas, and the western European plains. Between 1984 and 2023, the total surface water area exhibited a fluctuating decline, with PWBs, SWBs, and WPWBs decreasing by 97.2, 96.1, and 87 %, respectively. Conversely, SPWBs and WSWBs increased by 54.8 and 67.7 %, respectively. The degree of fragmentation varied over time, with higher fragmentation observed on the northern Iberian Peninsula, northwestern European plains, central Apennine Peninsula, and southern Balkan Peninsula. This study provides essential data for supporting biodiversity conservation, water resource management, and sustainable coastal development.